Laparoscopic cholecystectomy in situs inversus with partially intrahepatic gallbladder: a case report - Baxi, Kamakshi; Jha, Nitin; Khurana, Vibhu; Neeli, Dakshayani; Dogra, Loveneet (International Surgery Journal, 2023)
Situs inversus totalis (SIT) is a rare condition with mirrored visceral organs. Biliary colic has delayed diagnosis in this cohort of patients. Laparoscopic cholecystectomy (LC) in such condition is a technically challenging procedure and requires preoperative imaging. We report a case of a 37 years old lady with pain in left upper abdomen for last 1 year. Upon evaluation, she was diagnosed with cholelithiasis with SIT. MRCP was done to delineate the anatomy. The patient underwent LC in a split-leg position with mirrored port position by a right-handed surgeon. The duration of surgery was 90 minutes and the patient was discharged uneventfully in 48 hours and was well on one-week follow-up. LC is considered a safe surgery in patients with SIT. It requires an experienced surgeon, re-training of visual-motor coordination and modification of surgical steps.